DIAGNOSIS AND MANAGEMENT POST TRAUMATIC STRESS DISORDER IN SEXUAL ABUSE - Ni Made Apriliani Saniti (Universitas Udayana, 2013)
Traumatic experiences may happen anytime in our life. The more terrible the situation, the bigger chance for a person to have post traumatic psychological problem, that is the Post Traumatic Stress Disorder (PTSD). Sexual abuse is a kind of traumatic event that caused psychological trauma/stress for the victim. In order to be able to manage patient with PTSD, physician should comprehend properties regarding PTSD, including proper treatment and management.